Manajemen Proses Produksi Siaran Pemberitaan Media Televisi - Ine Fitrianingsih; Siti Abelia Puteri; Putri Handayani (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This research aims to find out what stages must be carried out during the production process, such as pre-production, implementation and post-production so as to produce quality and informative news broadcasts for the audience. The method used is the library research method, namely collecting various materials such as books, journals, magazines and literature related to research problems and objectives (Syahputra M.R. and Darmansah, 2020:21). News production in mass media and television plays an important role in informing the public. This process includes preparation, implementation and evaluation and is coordinated by production management. Television news typically follows the 5W1H format and covers genres such as entertainment, education, and news. This news channel is dedicated to providing up-to-date information carefully prepared by management.